Effect of atmospheric-pressure plasma jet on polycrystalline diamond micro-milling of silicon carbide. Issue 1 (2015) - Katahira, Kazutoshi; Ohmori, Hitoshi; Takesue, Shogo; Komotori, Jun; Yamazaki, Kazuo
Abstract A study was performed to investigate the effects of the application of an atmospheric-pressure plasma jet during polycrystalline diamond (PCD) micro- end-milling. A comparison was made between SiC surfaces after milling, with and without the application of the plasma jet. The plasma jet was found to allow the formation of a high-quality surface with an average roughness (Ra) of 0.73 nm. The proposed plasma jet is highly effective in improving both the chip formation process, by imparting hydrophilicity to the tool and workpiece surfaces, and removing surface contamination at the tool edge during machining.